George Pachymeres on King Milutin’s Brides and the Role of Queen Helen - Stanković, Vlada M. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The importance of diplomatic marriages for position and politics of Serbian king Milutin found its significant place in the vast historical work of the learned Byzantine scholar George Pachymeres. Of particular significance is Pachymeres’ information of the role and the influence of Milutin’s mother Queen Helen, which demonstrates her unique position within the Serbian ruling family, and his superb understanding of the relations within the Serbian royal family.